Review: Sterilisasi Produk Farmasi Steril dengan Metode Through Flow Filtration dan Tangential Flow Filtration - I Gede Yudistira Perdangga Bandem; Kadek Adisthi Pradipthasari; Kadek Indra Aryani; Ni Luh Dian Senja Pratiwi; Putu Siska Angelina Pramesti; I Gusti Ngurah Agung Dewantara Putra (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The production of pharmaceutical sterile products requires strict procedures to minimize the risk of microbial, particulate and pyrogen contamination that can be harmful to the user's health. The selection of the right sterilization method is the key to achieving the desired stability of the final product. Filtration sterilization is one of the oldest methods used for pharmaceutical sterile products. There are two types of feed flow in the method, namely through flow filtration and tangential flow filtration. This review article is prepared through literature search and download of national or international journals with inclusion or exclusion criteria that have been set. Literature sources are accessed online from various sites such as Google Scholar and Pubmed in the range of 2014-2024. The keywords used for journal searches are sterilization, through flow filtration, and tangential flow filtration. This review article reviews and compares the two methods to understand the differences, mechanism of action, and research objectives based on the review article on membrane filtration sterilization. This review aims to provide a better insight into the advantages and disadvantages of each membrane filtration sterilization method, as well as guidance in choosing the appropriate method based on the characteristics of the product to be sterilized. The results showed that through flow filtration is more commonly used in small volume and batch processes because of its simple design, but has limitations in reducing membrane fouling. In contrast, tangential flow filtration allows for continuous processing of larger volumes, with the advantage of minimizing particle build-up on the membrane surface, thus extending membrane life. The choice of method is also influenced by factors such as particle size, viscosity of the solution, sensitivity to heat, as well as operating costs. An in-depth understanding of the Working Principle and application of each method is essential for the pharmaceutical industry to ensure the quality, safety and efficiency of the production process. Thus, this review is expected to be a reference for researchers and practitioners in determining the optimal filtration sterilization strategy according to product needs.